2021
DOI: 10.1021/acssynbio.1c00006
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae Synthetic Transcriptional Networks Harnessing dCas12a and Type V-A anti-CRISPR Proteins

Abstract: Type V-A anti-CRISPR proteins (AcrVAs) represent the response from phages to the CRISPR-Cas12a prokaryotic immune system. CRISPR-Cas12a was repurposed, in high eukaryotes, to carry out gene editing and transcription regulation, the latter via a nuclease-dead Cas12a (dCas12a). Consequently, AcrVAs were adopted to regulate (d)­Cas12a activity. However, the usage of both dCas12a-based transcription factors and AcrVAs in the yeast Saccharomyces cerevisiae has not been explored. In this work, we show that, in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 66 publications
5
32
0
Order By: Relevance
“…Previous studies in other organisms, including bacteria, yeast and mammalian cells, already demonstrated the potent anti-Cas9 effect of AcrIIA4 (Li et al, 2018;Nakamura et al, 2019;Rauch et al, 2017). Recently, Yu and Marchisio (2021) also reported the high anti-Cas12a inhibitory capacity of AcrVA1 in yeast.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies in other organisms, including bacteria, yeast and mammalian cells, already demonstrated the potent anti-Cas9 effect of AcrIIA4 (Li et al, 2018;Nakamura et al, 2019;Rauch et al, 2017). Recently, Yu and Marchisio (2021) also reported the high anti-Cas12a inhibitory capacity of AcrVA1 in yeast.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, development of anti-Cas12a activities in planta can offer new possibilities for gene regulation. Anti-Cas12a protein AcrVA1 has been described to cleave the crRNA when bound to Cas12a preventing editing and CRISPRa in yeast and mammalian cells (Kempton et al, 2020;Yu and Marchisio, 2021;Figure 1e). Following the same procedure as described for AcrIIA4, we selected two targets previously characterized for Cas12a: XT1 and FT genes (Bernab e-Orts et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…From the third to the eighth group, the promoters are rather weak (see Tables S4–S6 ). The strongest of them almost matches a different synthetic promoter constructed in our lab (termed genCYC1t_pCYC1noTATA [ 26 ]) that we recently used to study the activity of type V anti-CRISPR proteins in S. cerevisiae [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The strongest MLPcore* expressed a 28.3-fold higher fluorescence than the weakest pTKcore* (see Figure 2 C). Interestingly, MLPcore* turned out to be 1.9-fold stronger than the constitutive TEF1 promoter—widely employed in yeast synthetic gene circuits—whereas the pTKcore* strength was comparable with that of the weakest synthetic promoter previously built in our lab and termed “truncated_pCYC1”, where we just shortened pCYC1 5′UTR down to 24 nt [ 37 ] (details about the number of TSSs activated by each of these promoters and the distance between TSSs and the TATA box are presented in Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ [113] , [114] , [115] ], The baker's yeast, moreover, is commonly treated as a cell factory to host heterologous pathways (such as that for β-carotene biosynthesis [ 60 , 112 ]) and as a chassis for synthetic networks that make use of the interactions between transcription factors derived from nuclease-deficient Cas protein and their antagonist anti -CRISPR macromolecules (see Fig. 4 ) [ 109 , 111 ]. Beekwilder and coworkers [ 112 ] introduced in S. cerevisiae a polycistronic vector that carried three β-carotene biosynthesis genes: crtI, crtE, and crtYB, to engineer a carotenoid pathway.…”
Section: Applicationsmentioning
confidence: 99%